1997
DOI: 10.1172/jci119486
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene D4 activates a chloride conductance in hepatocytes from lipopolysaccharide-treated rats.

Abstract: Endotoxin (LPS) can cause hepatocellular injury under several circumstances, and leukotrienes have been implicated as a contributing factor. Since ion channel activation has been associated with cytotoxicity, the aim of this study was to determine the circumstances under which LPS and/or leukotrienes activate ionic conductances in hepatocytes. LPS treatment of rats increased Cl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
(47 reference statements)
0
21
0
Order By: Relevance
“…We have previously shown that under specific cell culture conditions, inclusion of (leukotriene D 4 ) LTD 4 inside the patch clamp pipet activated chloride channels in hepatocytes. 13 This was observed in hepatocytes isolated from lipopolysaccharide (LPS)-treated rats and the effect could be reproduced by in vitro treatment of hepatocytes with conditioned medium from LPS-treated RAW 264.7 cells. Figure 1A shows the current-voltage (I-V) relationship of these LTD 4 -induced currents.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…We have previously shown that under specific cell culture conditions, inclusion of (leukotriene D 4 ) LTD 4 inside the patch clamp pipet activated chloride channels in hepatocytes. 13 This was observed in hepatocytes isolated from lipopolysaccharide (LPS)-treated rats and the effect could be reproduced by in vitro treatment of hepatocytes with conditioned medium from LPS-treated RAW 264.7 cells. Figure 1A shows the current-voltage (I-V) relationship of these LTD 4 -induced currents.…”
Section: Resultsmentioning
confidence: 98%
“…18 Conditioned medium, containing a cytokine mixture, was derived from the supernatant of RAW 264.7 cells by the method originally described by Cerami et al 19 as previously described. 13 In some experiments this medium was added to the hepatocyte cultures at a dilution of 1:5. TR-rats were donated by Dr. J.L.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 One postulated mechanism is the activation of chloride conductance in hepatocytes. 3 An interesting new aspect of Cys-LT-induced liver injury in cholestasis is described here. After BDL, Cys-LTs can no longer be excreted via the bile.…”
Section: Discussionmentioning
confidence: 97%
“…[1][2][3] Accordingly, the inhibition of leukotriene synthesis or the blockade of cysteinyl-leukotriene (Cys-LT) receptor 1 has been shown to protect against liver injury. 4,5 However, elevated leukotriene synthesis is not detected in all forms of acute liver injury.…”
mentioning
confidence: 99%